Biocompatibility and immunogenic response to recombinant honeybee silk material. Issue 8 (1st May 2019) - Sutherland, Tara D.; Vashi, Aditya V.; Kardia, Egi; Sriskantha, Alagacone; Rapson, Trevor D.; Hall, Robyn N.; Werkmeister, Jerome A.
Abstract: If tolerated in biological environments, recombinant structural proteins offer the advantage that biological cues dictating cell attachment and material degradation can be modified as required for clinical application using genetic engineering. In this study, we investigate the biological response to materials generated from the recombinant honeybee silk protein, AmelF3, a structural protein that can be produced at high levels by fermentation in Escherichia coli . The protein can be readily purified from E. coli host cell proteins after transgenic production and fabricated into various material formats. When implanted subcutaneously according to International Standard ISO 10993 tests, materials generated from the purified recombinant protein were found to be noncytotoxic, inducing a transient weak immunogenic response and a chronic inflammatory response that resolved over time. While preliminary, this study supports the ongoing development of materials generated from this protein for biomedical applications. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 107A: 1763–1770, 2019.